Effects of Water, Sanitation, Handwashing, and Nutritional Interventions on Child Enteric Protozoan Infections in Rural Bangladesh: A Cluster-Randomized Controlled Trial. (13th April 2018) - Lin, Audrie; Ercumen, Ayse; Benjamin-Chung, Jade; Arnold, Benjamin F; Das, Shimul; Haque, Rashidul; Ashraf, Sania; Parvez, Sarker M; Unicomb, Leanne; Rahman, Mahbubur; Hubbard, Alan E; Stewart, Christine P; et al.
Abstract : The trial found that individual handwashing and sanitation interventions significantly reduced childhood Giardia infections. Combined interventions provided no additional benefit. To reduce Giardia infection, individual interventions may be more feasible and cost-effective than combined interventions in similar rural, low-income settings. Abstract: Background: We evaluated effects of individual and combined water, sanitation, handwashing (WSH), and nutritional interventions on protozoan infections in children. Methods: We randomized geographical clusters of pregnant women in rural Bangladesh into chlorinated drinking water, hygienic sanitation, handwashing, nutrition, combined WSH, nutrition plus WSH (N+WSH), or control arms. Participants were not masked. After approximately 2.5 years of intervention, we measured Giardia, Cryptosporidium, and Entamoeba histolytica prevalence and infection intensity by multiplex real-time polymerase chain reaction of child stool. Analysis was intention-to-treat. Results: Between May 2012 and July 2013, we randomized 5551 pregnant women. At follow-up, among 4102 available women, we enrolled 6694 children into the protozoan assessment. We analyzed stool from 5933 children (aged 31 months) for protozoan infections. Compared with 35.5% prevalence among controls, Giardia infection prevalence was lower in the sanitation (26.5%; prevalence ratio [PR], 0.75 [95% confidence interval CI, .64–.88]), handwashing (28.2%; PR, 0.80 [95% CI, .66–.96]), WSH (29.7%; PR, 0.83 [95% CI, .72–.96]), and N+WSH (26.7%; PR, 0.75 [95% CI, .64–.88]) arms. Water and nutrition interventions had no effect. Low prevalence of E. histolytica and Cryptosporidium (<2%) resulted in imprecise effect estimates. Conclusions: Individual handwashing and hygienic sanitation interventions significantly reduced childhood Giardia infections, and there were no effects of chlorinated drinking water and nutrition improvements in this context. Combined WSH interventions provided no additional benefit. To reduce Giardia infection, individual WSH interventions may be more feasible and cost-effective than combined interventions in similar rural, low-income settings. Clinical Trials Registration: NCT01590095.